2021
DOI: 10.1155/2021/4746609
|View full text |Cite
|
Sign up to set email alerts
|

Modular Irregular Labeling on Double-Star and Friendship Graphs

Abstract: A modular irregular graph is a graph that admits a modular irregular labeling. A modular irregular labeling of a graph G of order n is a mapping of the set of edges of the graph to 1,2 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The modular irregularity strength for some graphs have known, such as path, star, tree, cycle, gear graph [4] , fan graph [3] , and wheel graph [1] . Recently, Sugeng, et al have determined the modular irregularity strength of double stars and friendship graphs [12] .…”
Section: Modular Irregular Labelling On Dodecahedral Modified General...mentioning
confidence: 99%
“…The modular irregularity strength for some graphs have known, such as path, star, tree, cycle, gear graph [4] , fan graph [3] , and wheel graph [1] . Recently, Sugeng, et al have determined the modular irregularity strength of double stars and friendship graphs [12] .…”
Section: Modular Irregular Labelling On Dodecahedral Modified General...mentioning
confidence: 99%
“…Bača et al also determined the modular irregularity strength of the fan graph [5] and wheel [6]. Then Sugeng et al determined the modular irregularity strength of double-star and friendship graphs [7]. Tilukay determined the modular irregularity strength of the triangular book graph [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, Bača et al in [3] found the modular irregularity strength of wheels W n . Sugeng et al in [14] provided the results for the modular irregularity strength of double-stars S k,k and friendship graphs f n .…”
Section: Introductionmentioning
confidence: 99%